2021
DOI: 10.1159/000512028
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-Radiomic Analysis for Pretreatment Prediction of Objective Response to First Transarterial Chemoembolization in Hepatocellular Carcinoma

Abstract: <b><i>Background:</i></b> The preoperative selection of patients with intermediate-stage hepatocellular carcinoma (HCC) who are likely to have an objective response to first transarterial chemoembolization (TACE) remains challenging. <b><i>Objective:</i></b> To develop and validate a clinical-radiomic model (CR model) for preoperatively predicting treatment response to first TACE in patients with intermediate-stage HCC. <b><i>Methods:</i></b&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 65 publications
(57 reference statements)
5
55
1
Order By: Relevance
“…The prevalence of extrahepatic circulation in HCC is well-documented [ 1 ]. Initial studies on extrahepatic circulation in patients with HCC pointed towards the possibility of ligation of hepatic artery, a now obsolete treatment for HCC, as the causative factor [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of extrahepatic circulation in HCC is well-documented [ 1 ]. Initial studies on extrahepatic circulation in patients with HCC pointed towards the possibility of ligation of hepatic artery, a now obsolete treatment for HCC, as the causative factor [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, preoperative serum AFP may be an indirect indicator of tumor burden. In fact, several studies have reported that an elevated AFP serum level is one of the crucial factors heralding poor survival after surgical resection, radiofrequency ablation, and transcatheter arterial chemoembolization of HCC (31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…To date, radiomics has made impressive performances in tumour differentiation [ 43 , 44 , 45 ], prognosis evaluation [ 46 , 47 , 48 ], therapeutic effect evaluation [ 49 , 50 , 51 , 52 ], and tumour metastasis evaluation [ 53 , 54 , 55 ]. Compared with the performance of traditional predictive models based on clinical data and imaging anatomy, better performance of radiomics has been widely reported [ 24 , 56 , 57 ].…”
Section: Pipeline Of Radiomicsmentioning
confidence: 99%